RB1 aberrations predict outcomes of immune checkpoint inhibitor combination therapy in NSCLC - Wang, Qian; Yu, Tao; Ke, Zi-Hao; Wang, Fu-Feng; Yin, Jia-Ni; Shao, Yang; Lu, Kai-Hua (Frontiers in Oncology, 2023)
Immune checkpoint inhibitors (ICI) have changed the treatment of non-small lung cancer (NSCLC). Furthermore, compared with monotherapy, ICI combination therapy had better efficacy and partly different mechanism. Therefore, we aim to investigate and improve biomarkers specialized for ICI combination therapy. We enrolled 53 NSCLC patients treated with ICI combination therapy and collected their tissue and plasma samples to perform next-generation sequencing (NGS) with a 425-gene panel. Results showed that the line of treatment was the only clinical factor significantly affecting objective response rate (ORR) and progression-free survival (PFS). Surprisingly, classical markers PD-L1 and TMB only had limited predictive values in the ICI combination therapy. Instead, we found RB1 mutation was significantly associated with prognosis. Patients with mutated RB1 had shorter PFS than those with wild RB1 (134d vs 219d, p=0.018). Subsequent analysis showed the RB1 related mutated cell cycle and chromosomal instability were also deleterious to prognosis (103d vs 411d, p<0.001; 138d vs 505d, p=0.018). Additionally, patients with more circulating tumor DNA (ctDNA) had significantly shorter PFS (41d vs 194d, p=0.0043). In conclusion, this study identified that NSCLC patients with mutated RB1 were less sensitive to ICI combination therapy. RB1 mutations and following cell cycle abnormalities and chromosomal instability can potentially guide clinical management.